Effect of fibre treatment on the properties of medium density fibreboard made from empty fruit bunches / Zawawi Ibrahim - Ibrahim, Zawawi (2017)
Natural fibres are widely used in the composite industry because of their availability and desirable properties. Malaysia being one of the largest producers of palm oil in the world generates empty fruit bunch (EFB) that has potential of being used as fibrous raw material in the fibreboard industry. Pre-treatment on the EFB fibres is needed in order to produce acceptable fibre properties for medium density fibreboard (MDF). The objectives of this study are to evaluate the fibre properties with different chemicals and concentration levels and to determine of the effects of different chemicals, their concentration and fibre properties on the physical and mechanical properties of MDF, and finally to determine the optimum condition for the EFB fibres. Two types of chemicals that were used : sodium hydroxide (NaOH) and acid acetic. The EFB fibres were treated at 0.2, 0.4, 0.6 and 0.8% with NaOH and acetic acid, and the fibres were used in the MDF production. The results showed that fibre treated with NaOH tends to remove more residual oils, produced longer fibre with high aspect ratio and low cellulose content. However it produced higher hemicellulose content with lower tensile strength resulted in poor fibre surface, higher pH value and less sensitive towards acid compared to those fibres treated with acetic acid. The results also showed that both treatments resulted in different MDF performance, where acid acetic fibre produced good fibre characteristic and better panel’s properties. The optimum condition was 0.4% for NaOH and 0.6% for acetic acid in order to produced panels with good strength and better dimensional stability and meets the standard requirements of EN 622-5 2006 (Requirements for Ultra-light MDF board for use in dry conditions (Type UL2 MDF))